Different cell compositions and a novel somatic KCNJ5 variant found in a patient with bilateral adrenocortical adenomas secreting aldosterone and cortisol - Zhao, Liling; Wan, Jinjing; Wang, Yujun; Yang, Wenjun; Liang, Qi; Wang, Jinrong; Jin, Ping (Frontiers in Endocrinology, 2023)
Introduction This study aimed to explore the possible pathogenesis of a rare case of co-existing Cushing’s syndrome (CS) and primary aldosteronism (PA) caused by bilateral adrenocortical adenomas secreting aldosterone and cortisol, respectively. Methods A 41-year-old Chinese woman with severe hypertension and hypokalemia for 5 and 2 years, respectively, was referred to our hospital. She had a Cushingoid appearance. Preoperative endocrinological examinations revealed autonomous cortisol and aldosterone secretion. Computed tomography revealed bilateral adrenal adenomas. Subsequently, adrenal vein sampling and sequential left and right partial adrenalectomy indicated the presence of a left aldosterone-producing tumor and a right cortisol-producing tumor. Pathological examination included immunohistochemical analysis of the resected specimens. Secretions of aldosterone and cortisol were observed both in vivo and in vitro. Further, whole-exome sequencing was performed for DNA that was extracted from peripheral blood leukocytes and bilateral adrenal adenomas in order to determine whether the patient had relevant variants associated with PA and CS. Results Immunohistochemical staining revealed that the left adenoma primarily comprised clear cells expressing CYP11B2, whereas the right adenoma comprised both eosinophilic compact and clear cells expressing CYP11B1. The mRNA levels of steroidogenic enzymes (including CYP11B1 and CYP17A1) were high in the right adenoma, whereas CYP11B2 was highly expressed in the left adenoma. A novel somatic heterozygous missense variant—KCNJ5 c.503T > G (p.L168R)—was detected in the left adrenal adenoma, but no other causative variants associated with PA and CS were detected in the peripheral blood or right adrenocortical adenoma. In the primary cell culture of the resected hyperplastic adrenal adenomas, verapamil and nifedipine, which are two calcium channel blockers, markedly inhibited the secretion of both aldosterone and cortisol. Conclusion We present an extremely rare case of bilateral adrenocortical adenomas with distinct secretion of aldosterone and cortisol. The heterogeneity of the tumor cell compositions of aldosterone- and cortisol-producing adenoma (A/CPA) and somatic mutation of KCNJ5 may have led to different hormone secretions in the bilateral adrenal adenomas.